Low CD36 and LOX-1 Levels and CD36 Gene Subexpression Are Associated with Metabolic Dysregulation in Older Individuals with Abdominal Obesity - Madrigal-Ruíz, Perla-Monserrat (J Diabetes Res, 2016)
Background. Obesity study in the context of scavenger receptors has been linked to atherosclerosis. CD36 and LOX-1 are important, since they have been associated with atherogenic and metabolic disease but not fat redistribution. The aim of our study was to determinate the association between CD36 and LOX-1 in presence of age and abdominal obesity. Methods. This is a cross-sectional study that included 151 healthy individuals, clinically and anthropometrically classified into two groups by age (<30 and ≥30 years old) and abdominal obesity (according to World Health Organization guidelines). We excluded individuals with any chronic and metabolic illness, use of medication, or smoking. Fasting blood samples were taken to perform determination of CD36 mRNA expression by real-time PCR, lipid profile and metabolic and low grade inflammation markers by routine methods, and soluble scavenger receptors (CD36 and LOX-1) by ELISA. Results. Individuals ≥30 years old with abdominal obesity presented high atherogenic index, lower soluble scavenger receptor levels, and subexpression of CD36 mRNA (54% less). On the other hand, individuals <30 years old with abdominal adiposity presented higher levels in the same parameters, except LOX-1 soluble levels. Conclusion. In this study, individuals over 30 years of age presented low soluble scavenger receptors levels pattern and CD36 gene subexpression, which suggest the chronic metabolic dysregulation in abdominal obesity.